Development of a theoretical construct for teacher expertise in the Chinese context and identification of its components: A mixed-methods study - Cai, Yonghong; Li, Yanli; Tang, Runjia (Frontiers in Psychology, 2023)
Introduction Teacher expertise is a vital element of teaching quality. Examining what constitutes teacher expertise has important implications for the theoretical development and practical application of teacher expertise. The present study was conducted to develop a theoretical construct for teacher expertise in the Chinese context, identify its components, and verify the validity of this construct. Methods This study adopted an exploratory sequential mixed-methods design. To develop a construct for teacher expertise and identify its components, critical incident interviews were conducted with 102 primary and secondary school teachers. Grounded theory analysis was applied to code 621 stories from critical incident interviews. To verify the construct validity and discriminant validity, a survey of 1,041 teachers was conducted in 21 primary schools and 20 secondary schools in Hebei and Shanxi provinces. Confirmative factor analysis, Kruskal-Wallis test, and Mann-Whitney test were used to evaluate the validity of the construct. Results Knowledge structure, teaching ability, and professional development agency constituted the construct for teacher expertise. This construct had good construct validity and discriminant validity. Knowledge structure could not identify expertise. Teaching ability and professional development agency could differentiate between expert and non-expert teachers. Discussion Teacher expertise is a complex, multidimensional, and adaptive construct. The construct can be used as a valid and reliable instrument to identify and develop teacher expertise. Moreover, this study expands on prior studies and complements recent theoretical models describing teacher expertise.